Academic vs. integrated functional-context literacy programs: Responding to the needs of low literate clients of welfare. - Larry G. Martin (Adult Education Research Conference, 1997)
The "Personal Responsibility and Work Opportunity Reconciliation Act of 1996" promises to usher in a new era of literacy programming as practitioners attempt to design short-term programs that address the academic and employment needs of low-literate welfare recipients. A comparative analysis of academic and integrated literacy/occupational skills programs is presented.